Fluoride and Nitrate Levels in Ground Waters of Arid Districts of Rajasthan, India - Gopal, Ram; Bhargava, T N; Ghosh, P K; Rai, Sushila (Annals of Arid Zone, 2016)
Fluoride and nitrate toxicity has been studied in 760 groundwater samples of Barmer. Jaisalmer and Bikaner. Water resources map showing distribution of fluoride and nitrate in waters of these arid districts has also been presented. As per drinking water standards of WHO fluoride and nitrate toxicity is present in 55% and 37% waters, respectively. Based on our earlier studies the maximum allowable concentration of total dissolved solids upto 2000 mg/I, fluoride upto 2 mg/I and NO2 upto 100 mg/I have been recommended for potable waters in desert areas of Rajasthan.